Utilization of Digital Literacy Technology in English Language Course Institutions - Euis Istikomah Khoirunnisa; Fasfa Ayu Utami; Ilham Nawari; Isa Rakhmawati (Universitas Muhammadiyah Semarang, 2023)
Technological developments of education are increasingly influencing institution, such as English language courses. This study aims to determine the benefits that can be felt from the existence of digital literacy technology in English language course institutions. The method used in this research is a descriptive method through a literature review or literature study. According to Milya Sari and Asmendri (2020: 44) literature study is one of the research methods carried out by collecting information and data using various kinds of sources in the library, such as reference books, research results similar, previous articles, notes, and various reviews related to research problems. This literature study will produce secondary data. According to Edi Riadi (2016: 48) (in Meita Sekar Sari and Muhammad Zefri, 2019: 311), secondary data is data generated indirectly from the research object. The results of the study found that using digital literacy in English courses is beneficial for improving students' English skills, for example, by giving assignments to review and create an article, which can then be presented in learning activities. Thus, students can improve their knowledge, writing, and communication skills using English.